Chemically bubbled hollow FexO nanospheres anchored on 3D N-doped few-layer graphene architecture as a performance-enhanced anode material for potassium-ion batteries. Issue 2 (14th December 2018) - Tan, Qiwei; Li, Ping; Han, Kun; Liu, Zhiwei; Li, Yang; Zhao, Wang; He, Donglin; An, Fuqiang; Qin, Mingli; Qu, Xuanhui
Abstract : A facile chemical bubbling strategy to generate Fe x O@NFLG-240 as a performance-enhanced anode material for potassium-ion batteries. Abstract : High performance potassium-ion batteries (KIBs) are promising alternatives for electrochemical energy storage applications owing to the abundant supply and lower price of potassium resources compared with lithium. Therefore, in KIBs, high-capacity anode material, capable of reversible charging and stable potassium storage, is necessary to achieve better performance. Iron oxides are capable of delivering a competitively high specific capacity over a conversion-type mechanism, but its anodic electrochemical properties are hampered by low conductivity and rapid structural failure due to severe stress changes upon repeated K + uptake/extraction. In this regard, we put forward a readily scalable chemical bubbling strategy to realize in situ construction of hollow Fe x O nanospheres anchored on 3D N-doped few-layer graphene framework (Fe x O@NFLG-240) as anode material for nonaqueous KIBs. This Fe x O@NFLG-240 features a honeycomb-like hierarchical architecture packed with cross-linked graphene membranes as supporting template and conductive network, which provides accelerated transportation kinetics, abundant electrochemical active sites and improved contact with electrolyte. The hollow structure of the uniformly anchored Fe x O nanospheres could effectively alleviate the dramatic volume variation during potassiation/depotassiation owing to their interior void space. Moreover, the combination of pseudocapacitive contribution and dimethoxyethane (DME) based electrolyte further boost the electrochemical performance. Consequently, Fe x O@NFLG-240 delivers a superior capacity of 423 mA h g −1 at 50 mA g −1 over 100 cycles and exhibits a satisfactory rate performance even at 5 A g −1 with splendid cycling stability in ultra-long tests over 5000 cycles.